ANALYSIS OF INTIMATE AND FORMAL LANGUAGE STYLE IN THE DRAMA SCRIPT DEWI ANJANI - I Gusti Ngurah Agung Ari Aditya; Abdul Muhid; Muhlisin (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research analyzes and describes the intimate and formal language styles used in the fifth scene of the drama script Dewi Anjani, focusing on the interactions between Raden Nuna Putra Janjak, Dewi Anjani, and Datu Tuan. Drawing on Martin Joos's (1967) language style theory, this qualitative study employs a coding technique to identify and interpret relevant dialogues. The analysis of 22 key data points reveals that language style serves not only as a communicative tool but also as a powerful indicator of evolving character relationships. Initially, formal language dominates, signifying the absence of personal ties, hostility, and the assertion of authority. However, a significant shift to an intimate style occurs, reflecting a transformation from conflict to reconciliation and familial recognition. This transition enriches the dramatic meaning and narrative, illustrating how stylistic choices contribute to character development and the overall dramatic arc. The findings offer a deeper analytical framework for understanding the interplay of intimate and formal language in literary works and contribute to the theories on the function and impact of stylistic choices in dramatic narrative.